Goods Advertising, Urban Space, and the Moral Law of the Image - Coccia, Emanuele (Book collections on Project MUSE., 2018)
Objects are all around us - and images of objects, advertisements for objects. Things are no longer merely purely physical or economic entities: within the visual economy of advertising, they are inescapably moral. Any object, regardless of its nature, can for at least a moment aspire to be 'good,' can become not only an object of value but also a complex of possible happiness, a moral source of perfection for any one of us. This text argues that our relation to things is what makes us human. It shows how objects become the medium through which a city enunciates its ethos, making an ethical life available to those who live among them.